The Effectiveness of CIRC in Teaching Reading on Descriptive Text for Vocational High School Students - Wiratno, Wiratno; Huda, M. Alimul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This research investigates whether students instructed using the Cooperative Integrated Reading and Composition (CIRC) method achieve higher reading proficiency compared to those taught with the Grammar Translation Method (GTM). The study focuses on second-year students and employs a non-randomized pretest-posttest design within a quantitative research framework. Two groups serve as the experimental subjects. Data analysis is conducted using ANCOVA. Findings indicate that students taught with the CIRC method have an estimated marginal mean score of 73.587, while those taught with GTM have a score of 69.133. This suggests that the CIRC method leads to superior reading achievement. Based on these results, it is recommended that educators adopt the CIRC method to enhance reading skills.